Genus Calliophis of Asiatic coral snakes: A deficiency of venom cross-reactivity and neutralization against seven regional elapid antivenoms. (October 2016) - Tan, Choo Hock; Liew, Jia Lee; Tan, Kae Yi; Tan, Nget Hong
Abstract: Venoms of Calliophis bivirgata and Calliophis intestinalis exhibited moderate binding activities toward Neuro Bivalent Antivenom (Taiwan) but not the other six elapid monovalent or bivalent antivenoms available in the region. All antivenoms failed to neutralize C. bivirgata venom lethality in mice. The findings indicate the need to validate antivenom cross-reactivity with in vivo cross-neutralization, and imply that distinct antigens of Calliophis venoms should be incorporated in the production of a pan-regional poly-specific antivenom. Graphical abstract: Highlights: Venoms of Calliophis bivirgata and Calliophis intestinalis were studied. Methods included indirect ELISA and lethality neutralization in mice. Both venoms showed negligible cross-immunoreactivity against elapid antivenoms. C. bivirgata venom lethality in mice was not cross-neutralized by the antivenoms. There is implication on the production of a pan-regional poly-specific antivenom.